Pendampingan Pencegahan Perundungan (Bullying) melalui Pendekatan Nilai-Nilai Islam Sekolah Menengah Kecamatan Pace Nganjuk - Agus Tohawi; Mastur Mastur; Anik Indramawan; Leily Vidya Rahma; Muhamad Ali Anwar; Nur Fuad; Binti Latifatul Magfiroh (Eastasouth Journal of Effective Community Services, 2024)
This study explores the implementation of bullying prevention assistance through an Islamic values approach in middle schools in Pace District, Nganjuk. Bullying remains a significant issue in educational settings, negatively impacting students’ psychological well-being and the overall school climate. The program integrates Islamic values such as compassion, tolerance, self-control, and respect into school activities, curriculum, and counseling services. Qualitative methods, including classroom observation, interviews with teachers, and curriculum analysis, were used to assess the effectiveness of this approach. The findings indicate that embedding Islamic values in daily school life enhances students’ empathy, self-control, and mutual respect, contributing to a more harmonious and inclusive environment. The study also highlights the importance of teacher training, collaborative efforts among stakeholders, and the development of anti-bullying policies rooted in religious and moral education. These results suggest that an Islamic values-based approach can serve as an effective model for bullying prevention in similar educational contexts.